Keberadaan Ekosistem Ekonomi dan Keuangan Terhadap Pertumbuhan Pasar Modal Syariah di Indonesia - Yusuf, Yusuf; Hidayatullah, Syarif (Tasharruf : Journal of Islamic Economics and Business, 2022)
The existence of a good Islamic economic and financial ecosystem will grow the performance of Islamic financial institutions. Islamic capital market institutions that manage investment products are expected to be able to manage these assets in order to provide benefits in the form of a greater rate of return to investors. This study aims to analyze the existence of the Islamic economic and financial ecosystem in increasing the growth of the Islamic capital market in Indonesia. This qualitative descriptive study was written based on literacy studies. The conclusion of the study is that a good Islamic economic and financial ecosystem can grow the performance of capital market institutions in Indonesia in improving the welfare of investors